2019
DOI: 10.1101/691279
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of waking cortisol with DHEA and testosterone across the pubertal transition: Effects of threat-related early life stress

Abstract: Atypical regulation of the hypothalamic-pituitary-adrenal (HPA) axis is a putative mechanism underlying the association between exposure to early life stress (ELS) and the subsequent development of mental and physical health difficulties. Recent research indicates that puberty is a period of HPA-axis plasticity during which the effects of exposure to ELS on cortisol regulation may change. In particular, increases in the sex hormones that drive pubertal maturation, including dehydroepiandrosterone (DHEA) and te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…While we think that it is important to consider the impact of different types of ELS (e.g., neglect and threat) on neurophenotypes, including WM, from a dimensional perspective ( McLaughlin et al, 2020 ), very few participants in our sample endorsed experiences of neglect. In contrast, threat-related ELS exposure was more common in our sample, and co-exposure to different types of ELS exposure was high ( King et al, 2020 ). Although we did not have sufficient levels of neglect endorsement in our study to separate the effects of neglect from those of threat, we showed in our supplemental follow-up analyses that in four of the six tracts in which there was an interaction of age and ELS cumulative severity, there were also interactions of age and ELS threat severity.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…While we think that it is important to consider the impact of different types of ELS (e.g., neglect and threat) on neurophenotypes, including WM, from a dimensional perspective ( McLaughlin et al, 2020 ), very few participants in our sample endorsed experiences of neglect. In contrast, threat-related ELS exposure was more common in our sample, and co-exposure to different types of ELS exposure was high ( King et al, 2020 ). Although we did not have sufficient levels of neglect endorsement in our study to separate the effects of neglect from those of threat, we showed in our supplemental follow-up analyses that in four of the six tracts in which there was an interaction of age and ELS cumulative severity, there were also interactions of age and ELS threat severity.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, in a follow-up set of analyses we tested whether ELS experiences related to threat in particular might explain our findings. We calculated ELS threat severity using the same procedure described above for cumulative ELS severity (Section 2.2.1 ), but only included events associated with threat (e.g., domestic violence, bullying, physical and/or sexual abuse as in King et al, 2020 ). We did not assess the specific effects of neglect-related ELS because the endorsement of this form of adversity was low in the current sample (only present in 8 of 156 participants).…”
Section: Methodsmentioning
confidence: 99%
“…Our study adds to a small literature studying waking hormone levels and coupling, prior to stressful events of the day (Black et al., 2018; King, Colich, et al, 2019; Ruttle et al., 2015). Studies that have relied on waking hormone levels also typically reveal strong developmental effects on HPA‐HPG axes coupling, as we did here.…”
Section: Limitations and Future Directionsmentioning
confidence: 80%
“…Each of these endocrine axes, as well as their coupling, respond to an individual's environment, particularly to change, stress, or challenges (Bobadilla, Asberg, Johnson, & Shirtcliff, 2015; Dismukes, Johnson, Vitacco, Iturri, & Shirtcliff, 2015; Ruttle, Shirtcliff, Armstrong, Klein, & Essex, 2015). The directionality (positive vs. negative correlation) and magnitude (unit change in association) of HPA‐HPG axes coupling (measured by their hormonal outputs) varies based on a youth's family antecedents (Dismukes et al., 2015; King, Graber, Colich, & Gotlib, 2019; Ruttle et al., 2015), suggesting that investigating “coupling” can help elucidate how early family environments shape children's development and health trajectories at a mechanistic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation